(3GdGOGQI GdGMJQGajI ddehGQO GdHTQjIs - (3YeQ(B, (3GdWQGhfIs ((3YeGf(B:s (3OGQ GdHOGjI fGTQhf(B,s, 2011)
(3GdegGQGJ GdafjI , GdGfSGfjI h GdGOQGcjI aj GdGOGQI , edGeM Yed GdeOjQ h YehejI Yedg , eeGQSI GdbhI dOi GdbGFO h eOGNd OQGSI GdbjGOI , GdGfeGW GdbjGOjI h GdGJLGgGJ GdMOjKI ddbjGOI GdGOGQjI , JfejI GdegGQGJ GdSdhcjI ddbGFO GdGOGQj , GdeOjQ h OhQI GOGQI JWhjQ GdehGQO GdHTQjI , GOGQI GdehGQO GdHTQjI cfXGe eaJhM h Gdeaghe GdMOjK dgG h GdGgOGa GdMOjKI ddehGQO GdHTQjI , GdNdajI GdJGQjNjI dGOGQI GdehGQO GdHTQjI h eGPG fSJajO efgG , GdeOjQ h GdJNWjW GdGSJQGJjLj h GdGOGQI GdGSJQGJjLjI , YedjGJ GOGQI GdehGQO GdHTQjI h GdJNWjW GdGSJQGJjLj dgG , GdYhdeI h GdeJZjQGJ GdYGdejI GdMOjKI h GfYcGSGJgG Ydi GOGQI GdehGQO GdHTQjI , GdefXeGJ GdeJYdeI h GdJYde GdJfXjej h YedjGJ GOGQI GdeYQaI , GdJWhjQ GdGOGQj h GdehGQO GdHTQjI C GYOGO GdehGQO GdHTQjI h JgjFJgG ddJacjQ GdGHOGYj , eSJbHd GOGQI GdehGQO GdHTQjI(B.s
Keywords: (3EOGQI(B- (3GdehGQO GdHTQjIs; (3GdGOGQIs; (3Gdbhi GdYGedIs; (3GdehGQO GdHTQjIs